The Influence of Financial Development on Wealth Inequality in Capitalism: Fresh Evidence From Emerging Countries - Orhan Cengiz; Müge Manga (Croatian Economic Survey)
Our study focuses on how financial development (FD) affects wealth inequality (WI) in ten emerging countries from 1995 to 2020. These countries include Brazil, China, India, Indonesia, Malaysia, Mexico, the Philippines, South Africa, Thailand, and Türkiye. We analyzed the impact of economic growth (EG) and trade openness (TO) on WI using the augmented mean group (AMG) estimator. Our research showed that FD leads to an increase in WI among panel groups, particularly in Brazil, China, Mexico, and the Philippines. Additionally, EG and TO have a positive effect on WI for panel samples. We also found a two-way causality relationship between FD and WI, EG and WI, and WI and TO. Our paper concludes with a policy recommendation that government intervention is crucial in ensuring that lower-income individuals have equal access to financial assets.